Fundamentals of drafting technology - Madsen, David A. (Delmar Publishers, 1994)
A spin-off of the best-selling Engineering Drawing and Design by Madsen, this book covers the basics of equipment, media, reproduction, lettering and lines, geometric constructions, multi and auxiliary view descriptive geometry, manufacturing processes, dimensioning, fasteners, sections, and working drawings.